The Effect of Adding Waste Tire Rubber Powder on Asphalt Concrete of Highway Density - Sujatmiko, Heri; ., . (International Journal of Engineering and Technology, 2018)
Diseases in plants are something that can happen to many plants either caused by pests or other factors, the disease in plants can be detected based on the symptoms that appear on the plant before spreading to all plants, to recognize the symptoms and types of diseases contained in plants require plant experts or also by applying expert systems with expert knowledge base applied to the system by using certain methods such as certainty factor method. Expected results with the availability of this expert system to the user can help many users to detect diseases in plants.Â